The role of hypertension and diabetes mellitus on the etiology of middle cerebral artery disease. Issue 4 (20th March 2022) - Zhang, Changqing; Li, Zixiao; Liu, Liping; Pu, Yuehua; Zou, Xinying; Yan, Hongyi; Pan, Yuesong; Zhao, Xingquan; Wang, Yilong; Wang, Yongjun
Abstract: Background: Ischemic stroke (IS) caused by middle cerebral artery (MCA) disease is the most common type of IS caused by intracranial artery disease in the Chinese population. Hypertension and diabetes mellitus are the common risk factors of cerebral small vessel disease and large artery atherosclerosis (LAA). However, little is known about whether hypertension and diabetes mellitus had different correlations with the small artery occlusion (SAO) and LAA etiology of MCA disease. Therefore, our aim was to identify the predictors of the etiology of MCA disease. Methods: We consecutively enrolled 967 patients with noncardiogenic IS in unilateral MCA territory. Vascular risk factors and the clinical–radiologic features of IS were analyzed. The etiology of IS were classified as SAO or LAA according to the Stop Stroke Study Trial of Org 10172 in Acute Stroke Treatment classification criteria. Multivariable logistic regression was used to identify the differences in the predictors between SAO and LAA etiology of MCA disease. Results: Multivariable logistic regression identified male and hypertension as the predictors of the SAO etiology of MCA disease, however diabetes mellitus, repeated transient ischemic attack before the stroke, gaze palsy, aphasia, headache at admission, and disability at discharge as the predictors of the LAA etiology of MCA disease. Conclusion: Hypertension and diabetes mellitus are related with the different etiology of MCA disease. Abstract : Male and hypertension were the predictors of the small artery occlusion etiology of middle cerebral artery disease; however, diabetes mellitus, repeated transient ischemic attack before the stroke, gaze palsy, aphasia, headache at admission, and disability at discharge were the predictors of the large artery atherosclerosis etiology of middle cerebral artery disease. Therefore, hypertension and diabetes mellitus are related with the different etiology of middle cerebral artery disease.